The Influence of Problem-Based Learning Model on Learning IPS - Musdiani, Musdiani (Jurnal Ilmiah Peuradeun, 2018)
This research entitled: "The Influence of Problem-Based Learning Model on IPS (Social Education Science) learning outcomes in appreciating the history materials of grade fifth students at SD Negeri 46 Banda Aceh". The aim of this study is to determine the effect and student learning outcomes on appreciating the material of historical relics towards learning outcomes. This study is quantitative, while the method of the research is experimental. The population in this study were the students of class V-A and class V-B that consisted 60 students. Class V-A is as an experimental and class V-B as conventional learning model. The test was used to collect the data. It was analyzed by using t-test formula. The results of the data analysis showed that the students of the experimental class got the 80.5 score, while the students in the control class were 74.5 score. It shows that students in the experimental class have better learning outcomes than control class students. The t-count of analysis shown that the value of t-arithmetic = 2.15. While the t-table value = 2.00. This proves the value t- h itu n g â‰¥ t- ta b el. It can be concluded that there is a significant influence between the influences of problem-based learning model with the results of learning on appreciating the material of the historical relics for class fifth students at SD Negeri 46 Banda Aceh.